Histo-anatomic Aspects on Zea Mays L. Influenced by Hemp Shives Polyphenolic Extract - Corneliu Tănase (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2016)
The plant kingdom is an inexhaustible source of bioactive compounds with antioxidant character. It is known that, natural polyphenols are essential compounds in stimulating plant growth and development. The aim of this study was to identify the internal structure changes in maize (Zea mays L.) seedlings, under the influence of hemp shives polyphenolic extract. Hemp shives polyphenolic extract was characterized in terms of the total content of polyphenols and individual content by HPLC. Germination tests were carried out going through a standard procedure. In order to perform the histo-anatomical characterization, the vegetal material was fixed and preserved in alcohol 70%, following to be cut by hand microtome. The sections obtained were stained using double staining reagents: green - iodine and ruthenium red. It was observed, compared with the control, that hemp shives polyphenolic extract determines a good development of the root hairs and increase leading bundles number and central vessels metaxylem. Hemp shives polyphenolic extract in lower concentrations has positive effects on developed process of Zea mays L. plants that can be attributed to bioregulation properties.